Pengaruh Tingkat Kehadiran Pegawai dan Lingkungan Kerja Terhadap Kinerja Pegawai Puskesmas Adiarsa Kab. Karawang - Lisnawati; Suroso; Flora Patricia Anggela; Benny Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the current era of modernization and globalization, employee performance is a very important factor in determining the success of an organization. This study aims to analyze the effect of attendance levels and work environment on employee performance at the Adiarsa Health Center, Karawang Regency. The study was conducted with a quantitative approach using the applied method, namely quantitative through a verification approach. Data were collected through a questionnaire survey involving 53 employees of the Adiarsa Health Center, Karawang Regency, with a sampling technique using the saturated sampling method. Data analysis was carried out using SPSS software version 26, with the application of multiple linear analysis models and t-tests and F-tests at a significance level of 5%. The results showed that attendance levels had a partial effect on employee performance, with a t-count value of 2.372 which was greater than the t table of 2.008. In addition, the work environment was also proven to have an effect on employee performance, with a t-count value of 4.011 which also exceeded the t table. Simultaneously, the level of attendance and work environment have a significant influence on employee performance, indicated by the calculated F value of 28.067 which is greater than the F table of 3.187. The amount of contribution of the variables of the level of attendance and work environment to employee performance is 52.9%, while the rest, 47.1%, is influenced by other variables not included in this study.